COVID-19 Lessons From The Field: Toward A Pediatric Physical Therapy Telehealth Framework - Galia Daube Fishman; Jeananne Elkins (International Journal of Telerehabilitation, 2022)
Introduction: Telehealth is an established health service delivery method, yet little is known regarding pediatric physical therapy telehealth. We aimed to evaluate users’ experiences and create a framework for effective delivery. Methods: A pediatric physical therapists’ telehealth user survey was conducted. Results: Seventy-three respondents varied in years of experience and caseload. Most found telehealth easy to learn and use, and they believed the treatment they delivered was useful. Three main themes for successful treatments emerged and were organized into a framework for effective delivery: (1) caregivers’ involvement; (2) therapist telehealth ‘toolbox’ (sub-divided into: treatment management tools, and therapist-caregivers’ collaboration tools); and (3) telehealth client (child) characteristics. Conclusion: This study suggests a new framework for effective pediatric physical therapy telehealth delivery to support best practice, for use by administrators and therapists and recommends directions for further research.